72.3k views
2 votes
What is the value of g^-1(9)

What is the value of g^-1(9)-example-1

2 Answers

7 votes

g(x) = 6x - 3


Let g(x) = y:

y = 6x - 3


Make x the subject:

y = 6x - 3

6x = y + 3


x = (y + 3)/(6)


Replace y with x:


g^(-1)(x) = (x + 3)/(6)


Find g⁻¹(9):


g^(-1)(x) = \cfrac{x + 3}{6}


g^(-1)(9) = \cfrac{9 + 3}{6}


g^(-1)(9) = 2

Answer: 2



User Oranit Dar
by
6.1k points
3 votes
Hi there!

• g(x) = 6x - 3

Then,
if g(x) = y :-

y = 6x - 3

⇒6x = y + 3

⇒x =
\frac{\text{y} + 3}{6}

According to th' question :-

g⁻¹(x) =
\frac{\text{x} + 3}{6}

g⁻¹(9) =
(9 + 3)/(6)

g⁻¹(9) =
(12)/(6)

g⁻¹(9) = 2

Hence,
The required answer is g⁻¹(9) = 2

~ Hope it helps!
User Wgm
by
6.8k points